Bilayer sol-gel system for local prevention in prosthetic joint infections and osteointegration improvement - Antonia Jiménez-Morales; Ángela Solís-Garrido; Beatriz Toirac; Aranzazu Mediero; Bruna Costa; Francisca Mulero; Óscar Murillo; Miguel Monclús; Jaime Esteban; John Jairo Aguilera-Correa (Communications Materials)
Abstract Prosthetic joint infection (PJI) is one of the most severe complications associated with arthroplasties. Here we evaluate a bilayer coating system designed for both PJI prevention and osteoinduction. The outer layer is loaded with levofloxacin and linezolid, providing broad-spectrum antibiotic effects in the short term, while the inner layer, loaded with dipyridamole, promotes osteointegration. We then deposit the coatings onto powder-metallurgical titanium substrates. The antibacterial outer layer effectively inhibits biofilm formation and planktonic bacterial growth, targeting both Gram-positive and Gram-negative bacteria. The osteostimulating inner layer, containing the highest dipyridamole concentration, enhances in vitro mineralisation. In vivo the bilayer system significantly reduces infection symptoms and bacterial load in the femur of S. aureus-infected mice with coated implants. Additionally, it promotes bone metabolism at the implant-bone interface, resulting in increased bone mineral content and density.